Evaluasi Kejadian Kecelakaan Kerja dan Kegagalan Produksi Menggunakan Metode Fault Tree Analysis (FTA) di PT MP - Asri Febi Wulandari; Suwarto Suwarto; Naomi Naomi; Setiawan Setiawan (JURNAL BIDANG ILMU KESEHATAN, 2025)
PT MP is a wheat flour processing company that has faced recurring workplace incidents and production disruptions over the past five years. These conditions have affected worker safety, operations, and product quality. Fault Tree Analysis (FTA) was selected as the primary method because it enables logical and systematic mapping of cause–effect relationships to design measurable, data-driven preventive actions tailored to workplace risks. This study aimed to identify the root causes of workplace accidents and production failures using FTA and to structure causal relationships clearly. Employing a qualitative case study design, data were collected through in-depth interviews, field observations, and documentation of K3L reports, HIRADC, and production processes, with validity tested via source triangulation. The findings revealed that workplace accidents were mainly caused by human factors such as lack of focus, fatigue, and non-compliance with SOPs, alongside environmental conditions. Production failures were linked to product contamination from insect infestation due to unstable storage temperatures and operational disruptions during the COVID-19 pandemic. The study concludes that implementing Occupational Health and Safety Management Systems (SMK3), sensor-based environmental controls, and stronger inter-unit coordination are essential for sustainable prevention strategies.